Frequency of Common Clinical & Laboratory Attributes in Newly Diagnosed Immune Thrombocytopenic Purpura - Aisha Nasir, Amna Shoukat, Hafsa Iqbal, Qurra-Tul-Ain, Ayesha Iqbal, Shizra Kaleemi, Talha Laique (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The adults ITP is often insidious & reveals diversity in the clinical course. These individuals usually seek medical help for muco-cutanaeous or subcutaneous bleeds, while the clinical picture can range from asymptomatic to life-threatening. Aim: To determine the frequency of common clinical and laboratory attributes in newly diagnosed immune thrombocytopenic purpura. Study Design: Descriptive cross sectional. Methodology: Present study was conducted at Pathology Department, Jinnah Hospital Lahore. A total of 95 patients with newly diagnosed immune thrombocytopenic purpura, age 20-50 years of both gender were included. Patients history of anticoagulant drugs or steroid use for last 1 month, CLD, CRF and post- radiotherapy or chemotherapy were excluded. After this, common clinical and laboratory attributes (hemorrhagic manifestations, hemoglobin levels, platelet count) in newly diagnosed immune thrombocytopenic purpura were noted. Data was analyzed using SPSS version 20. The chi-square tests was used to compare the groups. A p-value of 0.05 was considered significant. Results: Hemorrhagic manifestations in newly diagnosed immune thrombocytopenic purpura was found in 41 (43.16%) patients. The mean hemoglobin & platelets counts at presentation was 10.35 ± 1.43g/d l& 45.47 ± 2.07 x 109/l. Conclusion: It was concluded that hemorrhagic manifestations in newly diagnosed immune1thrombocytopenic purpura were found in about half of the patients.